2014
DOI: 10.1002/nvsm.1506
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder communication in service implementation networks: expanding relationship management theory to the nonprofit sector through organizational network analysis

Abstract: Nonprofits increasingly participate in government‐funded service implementation networks (SINs). However, extant research does not explore how organizations might strategically tailor communication to different stakeholder groups or use different communication tools for management. Stakeholders are not a monolithic group, and communicating with stakeholders within SINs is hypothesized to involve different forms of communication than communicating with stakeholders outside of the network. In this paper, relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
2
25
0
1
Order By: Relevance
“…Understanding where different types of posts and the use of differing media platforms (e.g., Facebook, blogging, Wikis, or Twitter) are most beneficial for an organization are both key to improving two-way communication. Peer networking with partner agencies, on the other hand, is a potentially useful benefit of social media if adopted with privacy and management concerns in mind (Maxwell & Carboni, 2014;Mergel & Greeves, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding where different types of posts and the use of differing media platforms (e.g., Facebook, blogging, Wikis, or Twitter) are most beneficial for an organization are both key to improving two-way communication. Peer networking with partner agencies, on the other hand, is a potentially useful benefit of social media if adopted with privacy and management concerns in mind (Maxwell & Carboni, 2014;Mergel & Greeves, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Her research focuses on emerging communications, nonprofit organizations and social policy. notes a network of organizations failed to adopt social media usage as a result of organizational policy (Maxwell & Carboni, 2014). A recent survey found that 74% of nonprofits using social media employ it as a megaphone for one-way engagement rather than a platform for strategic two-way communications.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonprofit organizational and public relations theories are coalescing as the use of Web 2.0 – a broad collection of social media applications that includes Facebook, Twitter, and YouTube, among others – becomes integrated into organizational communications repertoires (Carboni & Maxwell, ; Maxwell & Carboni, ; Saxton et al ., ; Sharma, ; Waters et al ., ). The broad availability and user‐friendly nature of social media platforms suggest that they may offer organizations enhanced opportunities to develop programs and messages that best support their publics, especially by way of stewardship behaviors.…”
mentioning
confidence: 99%